2016
DOI: 10.1016/j.euroneuro.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Abuse-related neurochemical and behavioral effects of cathinone and 4-methylcathinone stereoisomers in rats

Abstract: Cathinone and many of its analogs produce behavioral effects by promoting transporter-mediated release of the monoamine neurotransmitters dopamine, norepinephrine and/or serotonin. Stereoselectivity is one determinant of neurochemical and behavioral effects of cathinone analogs. This study compared effectiveness of the S(−) and R(+) enantiomers of cathinone and 4-methylcathinone to produce in vitro monoamine release and in vivo abuse-related behavioral effects in rats. For neurochemical studies, drug effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 27 publications
8
23
0
Order By: Relevance
“…As a result, the R (+) enantiomer displays a 50-fold greater selectivity than the S (−) enantiomer to promote monoamine release via DAT vs. SERT, and this stereoselectivity in neurochemical effects contributed to stereoselectivity in expression of abuse-related behavioral effects. It is unknown whether this stereoselectivity would also be apparent for other 4-R MCAT analogs, but a similar impact of stereochemistry was observed for isomers of 4-CH 3 cathinone [23]. Importantly, these results suggest that stereoselectivity at the chiral carbon at one end of the 4-R MCAT molecule can influence interactions of the 4-substituent at the other end of the molecule with its own portion of the DAT and SERT substrate-binding pockets.…”
Section: Stereoselective Effects Of Methcathinone and Mephedronementioning
confidence: 79%
See 1 more Smart Citation
“…As a result, the R (+) enantiomer displays a 50-fold greater selectivity than the S (−) enantiomer to promote monoamine release via DAT vs. SERT, and this stereoselectivity in neurochemical effects contributed to stereoselectivity in expression of abuse-related behavioral effects. It is unknown whether this stereoselectivity would also be apparent for other 4-R MCAT analogs, but a similar impact of stereochemistry was observed for isomers of 4-CH 3 cathinone [23]. Importantly, these results suggest that stereoselectivity at the chiral carbon at one end of the 4-R MCAT molecule can influence interactions of the 4-substituent at the other end of the molecule with its own portion of the DAT and SERT substrate-binding pockets.…”
Section: Stereoselective Effects Of Methcathinone and Mephedronementioning
confidence: 79%
“…The QSAR studies summarized above were conducted with racemic compounds, but more recent studies have identified an additional role for stereoselectivity as a determinant both of 4-R MCAT interactions with transporters and of ultimate expression of abuse-related effects [22, 23]. Specifically, methcathinone, methamphetamine, and many of their analogs possess a single chiral carbon atom (the α carbon signified by the asterisk in Fig.…”
Section: Stereoselective Effects Of Methcathinone and Mephedronementioning
confidence: 99%
“…Previously established ICSS studies on stereoselectivity of amphetamine and amphetamine-like compounds suggest a difference in isomer potency for compounds that are releasers at monoamine transporters. 3335 …”
Section: Discussionmentioning
confidence: 99%
“…The abuse-related potential of biogenic amine releasing agents appears to be related to their ability to promote greater release via DAT than via SERT such that DAT-selective agents possess higher abuse liability (see Negus et al, 2007 and Hutsell et al, 2016 for extended discussion). Consistent with this concept is that R (+)mephedrone with 50-fold selectivity for DAT over SERT produced in rats greater locomotor stimulation and rewarding properties as measured by conditioned place preference and facilitation of ICSS than its S (-)enantiomer which produced weak locomotor stimulation and lacked rewarding properties (Gregg et al, 2015).…”
Section: Current Sar Studiesmentioning
confidence: 99%
“…Consistent with this concept is that R (+)mephedrone with 50-fold selectivity for DAT over SERT produced in rats greater locomotor stimulation and rewarding properties as measured by conditioned place preference and facilitation of ICSS than its S (-)enantiomer which produced weak locomotor stimulation and lacked rewarding properties (Gregg et al, 2015). For 4-methylcathinone ( 53 ), R (+)53 was less potent than its S -enantiomer to promote release at DAT, but displayed slightly greater DAT versus SERT selectivity and produced abuse-related effects in ICSS (Hutsell et al, 2016). These studies (i.e., those reported by Gregg et al, 2015 and Hutsell et al, 2016) were the first to show the subtle stereochemical relationship between the ability of optical isomers of cathinone analogs to behave as substrates at DAT and SERT and their stimulant or rewarding actions.…”
Section: Current Sar Studiesmentioning
confidence: 99%